2022
DOI: 10.3389/fonc.2021.813063
|View full text |Cite
|
Sign up to set email alerts
|

FLASH Radiotherapy Using Single-Energy Proton PBS Transmission Beams for Hypofractionation Liver Cancer: Dose and Dose Rate Quantification

Abstract: PurposeThis work aims to study the dose and ultra-high-dose rate characteristics of transmission proton pencil beam scanning (PBS) FLASH radiotherapy (RT) for hypofractionation liver cancer based on the parameters of a commercially available proton system operating under FLASH mode.Methods and MaterialsAn in-house treatment planning software (TPS) was developed to perform intensity-modulated proton therapy (IMPT) FLASH-RT planning. Single-energy transmission proton PBS plans of 4.5 Gy × 15 fractions were optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…FLASH dose rates were also achieved and demonstrated to be an effective treatment in a human treated with a cutaneous T cell lymphoma [16], with treatment sparing normal skin and maximizing tumor control. This potential increase in the therapeutic ratio offered by FLASH has also attracted researchers to explore a wide range of FLASH-relevant topics on FLASH delivery techniques [17][18][19][20][21][22], mechanisms [23][24][25][26][27], and clinical translations such as treatment planning [28][29][30][31][32][33][34] and dosimetry [35][36].…”
mentioning
confidence: 99%
“…FLASH dose rates were also achieved and demonstrated to be an effective treatment in a human treated with a cutaneous T cell lymphoma [16], with treatment sparing normal skin and maximizing tumor control. This potential increase in the therapeutic ratio offered by FLASH has also attracted researchers to explore a wide range of FLASH-relevant topics on FLASH delivery techniques [17][18][19][20][21][22], mechanisms [23][24][25][26][27], and clinical translations such as treatment planning [28][29][30][31][32][33][34] and dosimetry [35][36].…”
mentioning
confidence: 99%
“…Here we chose a feasible cyclotron current for the Varian ProBeam system, and under this current, the FLASH coverage for both plans is close. We demonstrated earlier in (7,8) that a less minimum spot time in the FLASH spot map delivery will allow smaller MUs in the treatment plans at the fixed beam current, likely resulting in superior plan quality to ones with greater minimum spot times.…”
Section: A B D E Cmentioning
confidence: 92%
“…As proton beams shoot through the body instead of being stopped as in the conventional proton treatment plans, the dosimetric performances are also expected to be very different. Several studies have investigated proton pencil beam scanning (PBS) transmission planning in the lung ( 1 , 2 ), head and neck ( 4 , 5 ), brain ( 6 ), and liver patients ( 7 , 8 ). All of those studies have shown promising dosimetric outcomes using transmission beams, which helps to inform the characteristics of proton transmission beams for treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor in treatment planning is the number of beams and beam arrangement. Wei et al (40) studied the FLASH treatment planning for hypofractionation liver cancer cases by considering machine-related factors including beam current, minimum MU/spot, spot reduction, minimum spot time, and realistic plan-related factors including beam angular arrangement and number of fields. The results suggest minimum spot time and the number of beams are important parameters for the liver plans' FLASH dose rate coverage, target uniformity and coverage, and OAR dose constraints.…”
Section: Pbs Transmission Flash-ptmentioning
confidence: 99%